Embedded implementation research determinants in Latin American health systems - Rodrigo García-Cerde; Victor Becerril-Montekio; Étienne Langlois; Ludovic Reveiz; Jacqueline Alcalde-Rabanal; Pilar Torres-Pereda (Revista de Saúde Pública, 2021)
ABSTRACT OBJECTIVE: To assess the determinants of embedded implementation research (EIR) conduct in seven Latin American and Caribbean countries. METHODS: This qualitative interpretative study conducted and analyzed 14 semi-structured interviews based on a grounded theory approach using Atlas-ti© 7.5.7. We grouped the conditions appointed by interviewees as determinants of EIR conduct into six domains. RESULTS: The participation of high-level engaged decision makers as research co-producers is an important EIR determinant that fosters research use. Nevertheless, EIR faces challenges such as dealing with key personnel changes and fluctuating political contexts. CONCLUSIONS: Despite its limitations, EIR is effective in creating a sense of ownership of research results among implementers, which helps bridge the gap between research and decision-making in health systems.